The impact of the antibiotic resistance on the sustainable development - Barrantes Jiménez, Kenia (2021)
Antibiotic resistance (AR) is an increasingly complex public health problem, considered one of the greatest threats globally. The development of AR in bacterial pathogens is an expected consequence of evolutionary adaptation due to antimicrobials contamination in the environment. However, multiple factors are associated with the emergence and dissemination of AR, including excessive and poorly regulated use of antibiotics in human and animal medicine, agriculture, livestock, and industry, among other fields. The role of the environment as a reservoir for the generation and dissemination of AR genes and AR bacteria has recently been indicated. The approach to contain and control this problem involves multiple disciplines such as human and animal medicine, the environment, the industry, and the economy. This article describes the AR problem, the factors associated with its origin, and the multidisciplinary approach proposed for its management at a global level. Also, it will be described how AR affects sustainable development according to the UN 2030 Agenda, in compliance with some of the sustainable development goals.